Unités écologiques, « period rooms » : des ensembles d’objets mobiliers, de la collecte à la valorisation muséographique - Bénédicte Rolland-Villemot (In Situ)
Founded in 1937, the Musée national des Arts et Traditions populaires (national museum of folk art and traditions) has recently been transformed into the MuCEM, the Musée des Civilisations de l’Europe et de la Méditerranée, museum of European and Mediterranean Civilisations. This institution has always been concerned to link the collected artefact to an intellectual context, from the moment of its acquisition up to its display in a museum context. To achieve this, its teams developed a methodological tool of combined enquiry and collection that associated research with the collecting of objects, understood in the broadest sense of the word: physical objects, but also archives, sounds… and intangible cultural heritage. These are thus made up of ‘sequences’, coherent ecological units of ensembles of artefacts relocated in a museum. But these are first and foremost conceptual, intellectual constructions raising the question of their cultural sustainability.